Effects of inter-row spacing on growth, seed yield and yield components of Soybean (Glycine max) in Makurdi, Benue State-Nigeria - Iyorkaa, N.; Omoigui, L.; Ugbaa, M.S.; Ekeuro, G.C.; Odo, P.E. (2021)
Despite the numerous benefits of soybean, its grain yield per unit area in Nigeria is low estimated at 1.2 tons ha-1 compared to the worldwide average yield of 2.5 tons per hectare. The low yield is due in part to limited use of phosphorous fertilizer and poor crop management practices including low plant populations. Farmers in northern Nigeria including Benue State sow seeds in rows spaced 75cm. There has been little recommendation as to the exact row spacing that will give higher yield in soybean especially in Benue State. It is this gap that this research work seeks to address. This study was designed to determine the effects of row spacing on agronomic traits and yield of soybean in Makurdi, Benue state. The experiment was a 2 (row spacing) x 6 (soybean varieties) factorial arrangement laid out in a Randomized Complete Block Design (RCBD) with three replications.